A STRATEGIC MODEL FOR BUILDING COMPETITIVE ADVANTAGE IN PRIVATE ISLAMIC SECONDARY SCHOOLS IN SERANG CITY(A Multi-site Analysis of SMPIT Al Izzah and SMP Nuur El Bantany in Serang City) - Altaf Syauqy Iqbal Saifani; Andriyani; Andry Priharta (Adisam Publisher, 2026)
This study aims to identify the implementation of competitive advantage strategies, analyse internal school factors and external environmental pressures, and formulate a competitive advantage strategy model in private Islamic schools. The study employs a qualitative approach with a multi-site comparative design. Data were analysed using thematic interactive analysis supported by NVivo 12 software and SWOT analysis. Research data were obtained from subjects and informants consisting of headteachers, deputy headteachers for curriculum, teachers, students, school committees, and parents. Data collection techniques included in-depth interviews, observation, and documentation. The findings indicate that private Islamic schools have implemented strategic management in a practical and sustainable manner, in which competitive advantage strategies are developed through a hybrid approach. Schools do not adopt a single strategy in isolation; instead, they combine strategies contextually according to internal capacities and external pressures. Private Islamic schools are able to survive and grow not because they are free from constraints, but because they are capable of managing these limitations strategically. Further findings describe a continuous process within private Islamic schools that results in cost affordability, value-based differentiation, community loyalty, stability in student enrolment, and increased public trust. Another key finding, which can be interpreted within the competitive advantage strategy model, suggests that the sustainability of competitive advantage is determined not only by academic excellence but also by relational strength and social legitimacy. The proposed model demonstrates that private Islamic schools are able to build a strong competitive position through the integration of values, strategy, and operational implementation, whilst emphasising strategic flexibility as a key factor in their competitiveness. The contribution of this study lies in the development of a model that is both conceptual and applicable. Efforts to build competitive advantage do not rely on a single strategy, but rather on a combination of cost leadership, differentiation, and focus strategies.